Clinical characteristics and outcomes of COVID-19 in haematopoietic stem-cell transplantation recipients: an observational cohort study. Issue 3 (March 2021) - Sharma, Akshay; Bhatt, Neel S; St Martin, Andrew; Abid, Muhammad Bilal; Bloomquist, Jenni; Chemaly, Roy F; Dandoy, Christopher; Gauthier, Jordan; Gowda, Lohith; Perales, Miguel-Angel; Seropian, Stuart; Shaw, Bronwen E; et al.
Summary: Background: Haematopoietic stem-cell transplantation (HSCT) recipients are considered at high risk of poor outcomes after COVID-19 on the basis of their immunosuppressed status, but data from large studies in HSCT recipients are lacking. This study describes the characteristics and outcomes of HSCT recipients after developing COVID-19. Methods: In response to the pandemic, the Center for International Blood and Marrow Transplant Research (CIBMTR) implemented a special form for COVID-19-related data capture on March 27, 2020. All patients—irrespective of age, diagnosis, donor type, graft source, or conditioning regimens—were included in the analysis with data cutoff of Aug 12, 2020. The main outcome was overall survival 30 days after a COVID-19 diagnosis. Overall survival probabilities were calculated using Kaplan-Meier estimator. Factors associated with mortality after COVID-19 diagnosis were examined using Cox proportional hazard models. Findings: 318 HSCT recipients diagnosed with COVID-19 were reported to the CIBMTR. The median time from HSCT to COVID-19 diagnosis was 17 months (IQR 8–46) for allogeneic HSCT recipients and 23 months (8–51) for autologous HSCT recipients. The median follow-up of survivors was 21 days (IQR 8–41) for allogeneic HSCT recipients and 25 days (12–35) for autologous HSCT recipients. 34 (18%) of 184 allogeneic HSCT recipients were receiving immunosuppression within 6 months of COVID-19 diagnosis. Disease severity was mild in 155 (49%) of 318 patients, while severe disease requiring mechanical ventilation occurred in 45 (14%) of 318 patients—ie, 28 (15%) of 184 allogeneic HSCT recipients and 17 (13%) of 134 autologous HSCT recipients. At 30 days after the diagnosis of COVID-19, overall survival was 68% (95% CI 58–77) for recipients of allogeneic HSCT and 67% (55–78) for recipients of autologous HSCT. Age 50 years or older (hazard ratio 2·53, 95% CI 1·16–5·52; p=0·020); male sex (3·53; 1·44–8·67; p=0·006), and development of COVID-19 within 12 months of transplantation (2·67, 1·33–5·36; p=0·005) were associated with a higher risk of mortality among allogeneic HSCT recipients, and a disease indication of lymphoma was associated with a higher risk of mortality compared with plasma cell disorder or myeloma (2·41, [1·08–5·38]; p=0·033) in autologous HSCT recipients. Interpretation: Recipients of autologous and allogeneic HSCT who develop COVID-19 have poor overall survival. These data emphasise the need for stringent surveillance and aggressive treatment measures in HSCT recipients who develop COVID-19. Funding: American Society of Hematology; Leukemia and Lymphoma Society; National Cancer Institute; National Heart, Lung and Blood Institute; National Institute of Allergy and Infectious Diseases; National Institutes of Health; National Cancer Institute; Health Resources and Services Administration; Office of Naval Research.